Incidence of catastrophic health expenditures for households: An example of medical attention for the treatment of severe childhood malaria in Kinshasa reference hospitals, Democratic Republic of Congo - Félicien Ilunga-Ilunga; Alain Levêque; Samia Laokri; Michèle Dramaix (Elsevier, 2015)
Summary: This study aimed to estimate the incidence of catastrophic health expenditures faced by households in Kinshasa with children affected by severe malaria. A total of 1350 children below the age of 15 year who were hospitalized due to severe malaria were included in the study. We analyzed the incidence of households facing catastrophic expenditures according to two thresholds: 40% of the household's capacity to pay and 10% of the household's total consumption. Based on the '40% of the capacity to pay' threshold, the incidence of catastrophic health expenditures reached 81.1%, and this estimate reached 46.4% for the '10% above total consumption' threshold. Regarding the ≥40% capacity to pay threshold, the incidences of catastrophic expenditures was higher among households with children who were admitted to state hospitals (adjusted odds ratio [aOR] 3.7) and private hospitals (aOR 59.1), for poor households (aOR 13), for households with medium socioeconomic statuses (aOR 3.2), for female-headed households (aOR 2.9), for households with children affected by the neurological form (aOR 4.8) and respiratory distress (aOR 3.6), and for households who opted for a pre-hospital resort (aOR 2.7). Similar results were obtained when the 10% above the total consumption threshold was applied. Greater government financing of medical attention would lead to a reduction in the catastrophic health expenditures faced by the poorest households. Keywords: Catastrophic expenditures, Households, Severe malaria, Child